Role of maternal mortality epidemiological surveillance in decision mak ing - Távara Orosco, Luis (2015)
Epidemiological surveillance of maternal mortality (VEMM) is the component of health information system that facilitates the identification, reporting, identification and quantification of the causes of maternal death and the probability of its prevention in geographic areas and certain periods, with to contribute to the development of measures to reduce them. This review presents the steps VEMM guided by PAHO and the experience reported by the Ministry of Health with the system of maternal death VE operated in Peru since 1999 and its use for decision-making is reviewed .